Collaborative computing : networking, applications, and worksharing : 11th International Conference, CollaborateCom 2015, Wuhan, November 10-11, 2015, China. Proceedings /: networking, applications, and worksharing : 11th International Conference, CollaborateCom 2015, Wuhan, November 10-11, 2015, China. Proceedings. (2016) - Unknown
No abstract available